Implementation of sustainability accounting in medical waste management: An ethnomethodological approach - Mais, Rimi Gusliana; Rahmat, Nur; Wulaningsih, Ririn Widyastuti; Alfiana, Yeni; Oktasari, Erita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study explores how sustainability accounting practices improve hospitals’ operational, environmental, and social performance, particularly in medical waste management.Design/Methodology/Approach: Using an ethnomethodological approach, the research incorporates non-participant observation, in-depth interviews, and document analysis to understand how actors in the hospital environment interpret and implement sustainability accounting within daily routines.Research findings: The results show that medical waste management is conducted through systematic segregation, temporary storage, and third-party transportation, all supported by structured documentation, budgeting, and regular internal audits. Sustainability accounting emerges in the form of accountability records, cost reporting, and internal procedures that ensure compliance with environmental standards. However, its implementation tends to be reactive and focused on regulatory fulfillment rather than strategic sustainability enhancement.Theoretical contribution/Originality: This study highlights the role of sustainability accounting in strengthening hospital responsibility and transparency, while integrating ethnomethodology to uncover daily practices typically overlooked by quantitative approaches.Practitioner/Policy implication: The findings provide practical insights for hospitals to improve medical waste governance, strengthen ESG-based accountability, and enhance sustainability performance.Research limitation/Implication: The study is limited to a single hospital case and uses qualitative data, which may not be generalizable to all healthcare settings.